Predicting severity and restenosis in coronary artery disease - Firman, Doni (Heart Science Journal, 2026)
Despite significant advances in percutaneous coronary intervention (PCI), in-stent restenosis (ISR) remains a major challenge in contemporary coronary intervention. As a complication that is caused by multiple factors, identification of underlying mechanisms is crucial to prevent the event of ISR. A recent data highlights the Tp-e/QTc ratio on a standard ECG as a simple, non-invasive surrogate for SYNTAX score, suggesting a simple, non-invasive marker for coronary lesion complexity. Integrating pre-procedural assessment of coronary disease severity with post-procedural identification of independent risk factors may improve risk stratification and potentially reduce the incidence of ISR. Combined with aggressive secondary prevention strategies, this comprehensive approach may contribute to improved long-term outcomes after PCI.